2021
DOI: 10.1177/23821205211044607
|View full text |Cite
|
Sign up to set email alerts
|

Intern Orthopedic Rotation Versus Emergency Medicine Procedure Month: Which one Derives More Opportunity?

Abstract: INTRODUCTION The American College of Graduate Medical Education (ACGME) defines 18 “key procedures” as requirements in emergency medicine (EM) residency programs. The post-graduate year-1 (PGY-1) curriculum provides an early foundation for EM trainees to gain procedural experience, but traditional PGY-1 rotations may not provide robust procedural opportunities. Our objective was to replace a traditional orthopedic rotation with a 4-week rotation that emphasized EM procedure acquisition and comprehension. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Complicating standardization further are findings by others, such as Schmitz et al, who found key differences between the ortho education received by EM residents based on the time of day, components of the rotation, amount of resident autonomy, and patient volumes [9]. Another study that compared rotation structure by Briggs et al found that both dedicated ortho rotations in the ED and primary care sports medicine rotations provided experiences comparable to rotations in an ortho department for EM residents [10]. Despite the potential for these alternative structures to be feasible options for EM residency programs to utilize for their trainees' clinical ortho experiences, we believe that specific guidelines written in the form of both educational and clinical expectations are required to ensure that EM residents graduate with the competence to manage all orthopedic related complaints effectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Complicating standardization further are findings by others, such as Schmitz et al, who found key differences between the ortho education received by EM residents based on the time of day, components of the rotation, amount of resident autonomy, and patient volumes [9]. Another study that compared rotation structure by Briggs et al found that both dedicated ortho rotations in the ED and primary care sports medicine rotations provided experiences comparable to rotations in an ortho department for EM residents [10]. Despite the potential for these alternative structures to be feasible options for EM residency programs to utilize for their trainees' clinical ortho experiences, we believe that specific guidelines written in the form of both educational and clinical expectations are required to ensure that EM residents graduate with the competence to manage all orthopedic related complaints effectively.…”
Section: Discussionmentioning
confidence: 94%
“…While several attempts have been made to define content better or build standardized curricula for musculoskeletal/orthopedic topics, these efforts have not generalized well across programs since offerings of orthopedic content and training are contingent upon the unique set of resources available to a program or institution [9][10][11][14][15]25]. Chow et al proposed a standard ortho curriculum that included goals, objectives, and educational strategies that could be adapted to any educational setting [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation